2020
DOI: 10.2147/jpr.s247827
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mechanism of Traditional Chinese Medicine in Treating Knee Osteoarthritis</p>

Abstract: Knee osteoarthritis (KOA) is a degenerative disease, making a unique contribution to chronic pain, edema, and limited mobility of knee joint. Traditional Chinese Medicine (TCM) is a common complementary therapy for KOA and has been found effective. The aim of this review is to consolidate the current knowledge about the mechanism of four interventions of TCM: acupuncture, moxibustion, herbs, and massage in treating KOA, and how they alleviate symptoms such as pain, swelling, and dysfunction. Furthermore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 70 publications
0
65
0
1
Order By: Relevance
“…Acupuncture has been used in diabetes for a long time in Asian countries and recent studies have also suggested that acupuncture may alleviate SO (197)(198)(199). A randomized controlled trial, using electrical acupuncture coupled with essential amino acid supplementation to treat SO in male older people, has indicated that both electrical acupuncture with oral essential amino acids group and oral essential amino acids alone group can decrease BF% and increase ASM/H2, with the combination group being more effective than another group.…”
Section: Acupuncturementioning
confidence: 99%
“…Acupuncture has been used in diabetes for a long time in Asian countries and recent studies have also suggested that acupuncture may alleviate SO (197)(198)(199). A randomized controlled trial, using electrical acupuncture coupled with essential amino acid supplementation to treat SO in male older people, has indicated that both electrical acupuncture with oral essential amino acids group and oral essential amino acids alone group can decrease BF% and increase ASM/H2, with the combination group being more effective than another group.…”
Section: Acupuncturementioning
confidence: 99%
“…IL-1β is one of the most important pro-inflammatory cytokines in various inflammatory diseases including OA, acting as a trigger of the cascades of inflammatory responses. Also, IL-1β has been demonstrated to have a strong effect on chondrocyte senescence (23). McP-1 also plays a pivotal role in the development of OA by recruiting immune cells and promoting inflammation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Celecoxib has relatively small side effects and is widely used in the treatment of OA [32,33]. In recent years, more and more researches on herbal extracts and dietary supplements have opened up new horizons for the treatment of OA [34][35][36]. Curcumin down-regulates TNF-α by inhibiting the proliferation of macrophages and participates in the activation of brinolysis, so it provides a good complementary therapy for canine OA treatment [11].…”
Section: Paragraphmentioning
confidence: 99%